The induction motor's monitoring and protection system against vibration disturbances - Najmi, Muhammad; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
The industrial arena, the use of induction motors is an important element used in various aspects of industrial activities. Prolonged operation of an induction motor can lead to various mechanical failures. Mechanical failures can be identified by monitoring abnormal vibrations in motor components. Vibration monitoring is carried out using a vibration sensor, the ADXL345 accelometer sensor, which is attached to the induction motor body. The measurement results from this sensor are processed on the Arduino Mega and visualized into graphs on the ILI9341 TFT LCD. The vibration monitoring system is equipped with an induction motor protection device using a relay connected to coil A1 of the contactor. The contactor functions to cut off the electrical voltage from the 3-phase AC source to the induction motor being monitored. The relay will protect the induction motor when abnormal vibrations with an amplitude value of >3 g are found. System testing uses an induction motor connected to a VSD to vary the induction motor frequency. The results of the monitoring test are obtained and the vibration value will increase as the frequency of the applied voltage is increased and when the frequency is increased to 35Hz the maximum vibration detected is with a value of 3.75g, then the relay cuts off the voltage on the contactor coil and deactivates the induction motor